Dampak Adopsi International Financial Reporting Standards (IFRS) Terhadap Konservatisme Informasi Akuntansi pada Perusahaan di Indonesia - Ratna Puji Astuti; Agus Kuntoro (Jurnal Ilmiah ESAI, 2018)
The objective in this study is to examine empirically changes in the level of conservatism of corporate accounting information in Indonesia as a result of the use of Financial Accounting Standards (IFRS) adopted by IFRS (International Financial Reporting Standards). Conservatism was measured using the Market-to-Book bias component model (Beaver and Ryan, 2000). This study uses the Financial Statement data from 178 companies, 2007 to 2016, listed on the Indonesia Stock Exchange. Using multiple regression models that place accounting conservatism as a dependent variable while IFRS adoption, managerial ownership, institutional ownership, and public ownership as independent variables, this study proves that IFRS adoption does not affect the level of conservatism of accounting information. The size of the firm (size) and the composition of debt (leverage) is a control variable that participates in controlling the model of this study.Â Keywords: IFRS adoption, conservatism of accounting information.